2018
DOI: 10.1371/journal.pone.0205070
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic pathway and optimal conditions for the production of indole-3-acetic acid by an endophytic fungus, Colletotrichum fructicola CMU-A109

Abstract: Endophytic fungi are known to produce indole-3-acetic acid (IAA), which can stimulate plant growth. Twenty-seven isolates of endophytic fungi were isolated from Coffea arabica in northern Thailand. Only one isolate (CMU-A109) produced IAA in vitro. This isolate was identified as Colletotrichum fructicola based on morphological characteristics and molecular phylogenetic analysis of a combined five loci (internal transcribed spacer of ribosomal DNA, actin, β-tubulin 2, chitin synthase and glyceraldehyde-3-phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 54 publications
6
47
0
1
Order By: Relevance
“…This is in agreement with previous reports, which showed that endophytic inoculation to the host plants resulted in the improvement of growth and stress tolerance [26][27][28]. However, the elongation of rice, corn and rye coleoptile segments induced by the crude IAA extract of C. fructicola endophyte were not statistically different from those of the pure IAA treatments, but the values were significantly higher than the control (distilled water) treatment [46].…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with previous reports, which showed that endophytic inoculation to the host plants resulted in the improvement of growth and stress tolerance [26][27][28]. However, the elongation of rice, corn and rye coleoptile segments induced by the crude IAA extract of C. fructicola endophyte were not statistically different from those of the pure IAA treatments, but the values were significantly higher than the control (distilled water) treatment [46].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, IAA production by ECM fungi (S. sinnamariense and Suillus variegatus) and endophytic fungi (Colletotrichum fructicola, C. gloeosporioides, Tulasnella sp. and Muscodor cinnamomi) could stimulate oat and rice coleoptile elongations [29,32,[50][51][52]. IAA production from white rot fungus, Pleurotus ostreatus significantly increased the lengths of wheat coleoptile segments [53].…”
Section: Discussionmentioning
confidence: 99%
“…The crude ethyl acetate extract of the fungal indole metabolites was applied to thin layer chromatography (TLC) using silica gel G F254 aluminum (thickness 0.25 mm) plates (Merk, Germany). The plates were developed in a solvent mixture of nhexane:ethyl acetate:isopropanol:acetic acid (40:20:5:1, v/v/v/v) according to the method described by Numponsak et al [32]. Identification of indole compounds was also performed using chromogenic reagents by spraying with Ehmann's [33], Ehrlich's [33] and Salkowski's reagents on TLC plate and subsequent heating to 90˚C.…”
Section: Detection and Quantification Of Iaa And Related Indole Compomentioning
confidence: 99%
See 1 more Smart Citation
“…IAA is responsible for cell division and elongation responding to various factors as light, presence of pathogens etc. Fungi are able to use secreted IAA for interaction with plants in pathogenesis or symbiotic strategies, supporting the defense mechanism of plants [47][48][49][50][51][52]. Tryptophan is the main precursor for IAA synthesis and its presence increases the IAA production which in turn, enhances the availability of substrate for plants [50].…”
Section: Discussionmentioning
confidence: 99%